Analisis Pengembangan Usaha Kuliner Sebagai Peluang Usaha Rumahan di Desa Lau Gumba - Sanny, Annisa; Muhammad Toyib Daulay; Dhea Yulianisa (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
This research shows that culinary businesses, especially tanghulu strawberries, can increase business opportunities and the family economy in the application of the 4P marketing mix development strategy which includes strategies through products, namely producing products from local products, using traditional bamboo skewer equipment, not using food preservatives. Strategy through price, namely by setting prices according to the quality of the products produced and the market area. Furthermore, the promotion strategy is sales promotion by using banners, placing brand signs in front of the house, placing brand name stickers on the packaging, and selling directly to buyers. Furthermore, the distribution place strategy is to distribute culinary businesses directly to consumers. As for the obstacles faced by home-based entrepreneurs, where internally seen from the financial aspect, the capital used still comes from business owners, from the human resources aspect, namely the lack of knowledge about marketing methods and technology utilization. Furthermore, the infrastructure used is still very simple and traditional. While externally there is competition among home-based culinary business entrepreneurs.